Alterações metabólicas e histopatológicas de tecido lamilar do casco e da mucosa ruminal em bovinos submetidos a dietas com diferentes níveis de amido - Rodrigo Libério Araujo Palhano (2022)
Laminitis stands out among the diseases that affect the locomotor system. Despite being a multifactorial disease, nutritional management is still seen as having a critical role in the emergence of laminitis. However, the relationship between rumen acidosis and laminitis is questioned, as there is still no clarification of how ruminal acidosis could lead to histological changes in the hoof. Our objective was to evaluate the metabolic alterations caused by the consumption of confinement diets in steers and possible histological alterations in the hoof and other organs. Sixteen Holstein steers with an average initial live weight of 250 + 25.5 kg were used, separated into two groups that received diets with different amounts of starch, group AG (36.96% starch) and BG (16.81% of starch), evaluated over 91 days of confinement. Rumen parameters such as ruminal fluid pH and methylene blue reduction time were evaluated, as well as blood parameters such as glucose, insulin and IGF-1. The glucose tolerance test was performed on days 0, 39 and 102. A biopsy of the dermo-epidermal junction of the wall region of all animals was performed 40 days before the beginning of the experiment, and after slaughter, samples of the dermo-epidermal junctions were performed. epidermis from the wall and sole regions of the hoof were obtained and histologically processed by HE and PAS staining. Hemorrhage, inflammatory infiltrate, arteriovenous shunt in the dermis were evaluated. The morphology, length and width of the epidermal lamina, and the morphology of the epidermal cells, presence of irregularities in the basement membrane were examined by PAS staining. The high-grain diet reduced the animals' feeding and rumination time, decreased rumen fluid pH and methylene blue reduction time. In half of the animals in the group, the high-grain diet caused histological changes compatible with rumen acidosis, such as mild multifocal hydropic degeneration and intraepithelial microabscesses. The glucose area under the curve (AUC) did not differ between groups in the GTT Feedlot diets had higher insulin AUC during GTT at the end of experiment D 102. The two feedlot diets increased the IGF-1 levels of the animals, and the AG group had the greatest increase. Feedlot diets were able to reduce the length and width of the epidermal layers. The AG group increased the length of parakeratosis in the laminar tissue. Despite the fact that there were histological changes in the hooves, there was no significant difference between diets with different starch inclusions. Although there was no difference between the groups, the most common change in the shape of the epidermal laminae was the fringing. The increase in IGF1 and the increase in insulin AUC, caused by the confinement diets, may have favored the shortening of the epidermal laminae of the laminar tissue with disappearance of the keratinized axis with the proliferation of nucleated cells between the lamellar tissue and the beginning of the stratum corneum. that supposedly should not exist (parakeratosis), reducing the stability and quality of the lamellar tissue. Future studies with shorter adaptation time, longer challenge time with the diet with greater starch inclusion, and/or making the diets of different groups more diversified, analyzing the levels of IGF-1 should be conducted to investigate the relationship between ruminal acidosis subclinical, metabolic alterations and histological hoof alterations.